Utilizing Social Media to Promote Civic Engagement in the Social Studies Classroom. Issue 2 (4th March 2019) - Kenna, Joshua L.; Hensley, Matthew A.
Abstract: The United States of America's government relies on the people. Unfortunately, research illuminates a gradual decline in the civic and political participation among youth, ages 18-29, in the U.S. since the 1970s. While the decline takes shape in multiple forms other than voting, this article argues that teachers can improve students' civic engagement through the aide of social media. In order to achieve that goal, the article begins by defining civic engagement, especially within context of a digital age. Then describes three prominent classroom techniques for using social media found in the literature: micro-blogging, backchanneling, and virtual social networks. Finally, the article provides classroom-tested examples of how teachers can utilize the three techniques to promote the kind of civic and political engagement first defined.